Factors predicting preoperative anxiety among adult patients undergoing cardiac surgery in China: A cross-sectional study - Xing, Aizhen; Hengudomsub, Pornpat; Ponpinij, Panicha (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Preoperative anxiety is a significant concern for patients undergoing surgery, as it can lead to adverse effects such as increased postoperative pain, delayed wound healing, prolonged hospital stays, higher incidences of postoperative complications, and even mortality. Preoperative anxiety is particularly common in patients undergoing cardiac surgery, but it is often overlooked and warrants further investigation. Objective: This study aimed to explore preoperative anxiety and its predictors, including fear of surgery, preoperative sleep quality, perception of illness severity, and perceived social support among adult patients undergoing elective cardiac surgery. Methods: A cross-sectional study was conducted with 142 adult patients undergoing elective cardiac surgery using simple random sampling. Data were collected from patients in the Class III Grade A general hospital in Wenzhou, China, between October 2023 and March 2024. Questionnaires were used to gather information about patients’ demographic characteristics, fear of surgery, preoperative sleep quality, perception of illness severity, perceived social support, and preoperative anxiety. Descriptive statistics, Pearson correlation analysis, and multiple linear regression were employed for data analysis. Results: The total score for preoperative anxiety was 15.98 ± 4.95. Fear of surgery, preoperative sleep quality, perception of illness severity, and perceived social support explained 37.3% of the variance in preoperative anxiety (Adjusted R² = 0.373, F(4,142) = 26.77, p <0.05). Fear of surgery was the strongest predictor (β = 0.539, p <0.001), followed by preoperative sleep quality (β = -0.166, p <0.05) and perceived social support (β = -0.138, p <0.05). Perception of illness severity was not a significant predictor of preoperative anxiety. Conclusion: Preoperative anxiety in adult patients undergoing elective cardiac surgery is significantly influenced by factors such as fear of surgery, preoperative sleep quality, and perceived social support. Nurses can implement targeted interventions to reduce preoperative anxiety. These interventions may include addressing the fear of surgery through health education and psychological counseling. Furthermore, improving the hospital environment to promote a calm and quiet atmosphere can enhance sleep quality. Encouraging social support to help patients build confidence in the success of their surgery and their ability to recover is also recommended.